A Comparison of the Accuracy of Maples and Rice and Newly Derived Formula for Age Estimation: A Forensic Study - Bajpai, Manas; Mishra, Namita; Sharma, Parul (Journal of Orofacial Research, 2012)
Aims and objectives: The aim of the study was to study the physiological changes of teeth according to the Gustafson’s criteria by obtaining a new linear regression formula and compare it with Maples and Rice formula for age estimation. Materials and methods: Total of 70 cases who visited the department of oral and maxillofacial surgery for extraction were taken in the study for teeth collection and the age of the patients was noted. The following dental parameters were studied in each case; attrition, periodontal disease, cementum apposition, secondary dentine deposition, root translucency and root resorption. Total scores of different parameters were plotted against the total score were plotted and regression formula obtained and by the use of this formula ages were estimated. Maples and Rice formula was also applied in the same scores and ages estimated. Results: On comparing the means of both the calculated age and the actual age, it was observed that the difference between them was statistically significant except in the age group of > 70 years age group. On calculating the age mean error was found to be ± 4.52 and for Maples and Rice it was ± 6.43.